High-efficiency Nd:LuVO4 laser at 1343 nm recycling-pumped by a laser diode at 916 nm - Dai, Wantian; Liu, Tongyu; Ding, Yu; Zhao, Yuwei; Zhang, Yongning (Frontiers in Physics, 2024)
A high-efficiency Nd:LuVO4 laser, pumped by a fiber-coupled laser diode (LD) at 916 nm, was successfully demonstrated. Employing a recycling-pumping architecture, an output power of 12.1 W at 1343.2 nm was achieved with an incident pump power of 20 W, resulting in a slope efficiency of 62.1% and an optical conversion efficiency of 60.5%. Furthermore, the beam quality factor was measured to be approximately 1.1 at the maximum output level.